The impact of artificial hydric stress on understory ferns community in an ombrophylous forest in the eastern Amazon - Medeiros, Priscila Sanjuan de; Ferreira, Leandro Valle; Costa, Antônio Carlos Lôla da (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2014)
The ferns plants have highly dependence on moisture for reproduction and very sensitive to variations in meteorological conditions. The aim of this study was to compare the influence of artificial water stress in the species richness and density of individuals of ferns in the understory of the Amazon rainforest during the Dry Forest Project (Esecaflor). The Esecaflor project consists of two hectares, one hectare of experimental area, with exclusion of precipitation, and other hectare as a control. The experiment began in 2000 and is still active. Soil moisture was measured from 2000 to 2011 and data for ferns was collected in 2011. The reduction of soil moisture in the control area, compared to the control, ranged from 17% to 68%. The species richness varied from 12 to five in the control and experimental areas, respectively, a reduction of 58 %, while the density of individuals varied between 112 and 11 in the control and experimental areas, respectively, a reduction of 90%. The reduction in species richness and the density of individuals in the experimental area is due to the reduction of soil moisture. This demonstrates that climate changes in the Amazon generate negative impacts on biodiversity.